1999
DOI: 10.1007/bf02741375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol on calcium homeostasis in the nervous system

Abstract: Ethanol is a major health concern, with neurotoxicity occurring after both in utero exposure and adult alcohol abuse. Despite a large amount of research, the mechanism(s) underlying the neurotoxicity of ethanol remain unknown. One of the cellular aspects that has been investigated in relationship to the neuroteratogenicity and neurotoxicity of ethanol is the maintenance of calcium homeostasis. Studies in neuronal cells and other cells have shown that ethanol can alter intracellular calcium levels and affect vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 156 publications
1
15
0
Order By: Relevance
“…This may indicate a loss of vessel integrity and enhanced vascular shaping. Some of the effects of EtOH may also be modulated by its antiproliferative effect on astrocytes (Costa et al, 2004) or maintenance of calcium homeostasis (Catlin et al, 1999). Our data also show that cholesterol did not markedly affect the EtOH-induced changes.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate a loss of vessel integrity and enhanced vascular shaping. Some of the effects of EtOH may also be modulated by its antiproliferative effect on astrocytes (Costa et al, 2004) or maintenance of calcium homeostasis (Catlin et al, 1999). Our data also show that cholesterol did not markedly affect the EtOH-induced changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed for ethanol‐induced neuronal loss; these include: 1) inducing oxidative stress; 2) disrupting neurotrophic signaling and intracellular calcium homeostasis; 3) inhibiting the proliferation of neuronal precursors; and 4) altering neurotransmitter systems (Luo et al,1997; Webb et al,1997; Luo and Miller,1998; Catlin et al,1999; Ikonomidou et al,2000; Goodlett and Horn,2001; de la Monte and Wands,2002; Davies,2003; Kumral et al,2005). The action of alcohol is complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used 50 mM ethanol for sustained exposure to examine changes of L-type HVCCs because the previous studies demonstrated that 50 -100 mM ethanol in vivo is relevant to the blood ethanol concentrations in clinical populations (31). Moreover, the blood ethanol concentration in animals with ethanol physical dependence induced by sustained ethanol vapor administration employed here was about 290 mg / dl of blood (23), and this blood concentration is considered to be similar to 50 mM ethanol concentration in vitro.…”
Section: Discussionmentioning
confidence: 99%